E-Banking: Problems and Prospects an Empirical Study in Punjab - Uppal, R. K. (Information Management and Business Review, 2011)
The present study is concerned with the problems and prospects of e-banks in India. The present paper suggests some policies on the basis of perceptions of 60 selected e-bank employees regarding the various issues related to e-banking services. The paper concluded that not more then 50% of Indian bank customers are using e-channels, these channels are not much popular among old age and middle age persons as much as among youngsters and finally the paper concludes that the most of the customers are shifting from public sector banks to new private sector banks or foreign banks to avail innovative and attractive services. On the basis of these conclusions, paper suggests some strategies to make the public sector banks more competitive in the era of IT.